Global Distribution and Prediction of Transmission-Risk of Visceral Leishmaniasis - Xubin Wu; Xiaohui Wen; Shuxuan Song; Chenxi Zhao; Zhongjun Shao; Kun Liu; Ting Fu (Zoonoses, 2024)
Visceral leishmaniasis (VL) is a vector-borne disease posing increasing public health concerns. Although efforts to eliminate VL are underway, its global risk distribution remains unclear, because of changes in transmission risk. Worldwide province-level data on VL incidence were obtained from multiple sources. We analyzed the global evolution features of VL and estimated its ecological niches with boosted regression tree models. A risk map was generated to analyze regions with high VL risk. A total of 558 articles and 2,694 records from 310 provinces were included. The model indicated that precipitation in the warmest quarter and poor socio-demographic index were the most significant risk factors affecting VL distribution. The risk map indicated that Brazil, Iran, Ethiopia, and India were the regions with the highest probability of infection. We estimated that 5.3 billion people live in regions at risk of VL. VL is undergoing geographic expansion. Our study increases understanding of VL’s global-risk distribution and how risk factors influencing the disease transmission. Our findings may aid in promoting disease control in future surveillance activities.